Contextualizing Policy Adoption: A Case Study of Tuberculosis Control Policy in Depok City - Ayuningtyas, Tri Auri Putri; Bachtiar, Adang (Journal of Indonesian Health Policy and Administration, 2025)
This study analyzes the formulation and implementation process of Depok Mayor Regulation No. 61 of 2023 on Tuberculosis (TB) Control using Friedman’s legal system theory (1975) and the eight General Principles of Good Governance (Asas Umum Pemerintahan yang Baik – AUPB). The regulation provides a comprehensive framework, encompassing promotive, preventive, curative, and rehabilitative aspects to support TB control. The legal structure includes the establishment of a cross-sectoral Tuberculosis Control Acceleration Team, involving government agencies and community organizations. Findings reveal that while the regulation has fulfilled several AUPB principles, such as legal certainty, utility, and public interest, there are areas requiring improvement. These include strengthening a culture of collaboration, clearly defining responsibilities among stakeholders, and enhancing transparency. Furthermore, the analysis highlights the need for ongoing evaluation and adjustments to address challenges in implementing the policy effectively. This study concludes that while Depok Mayor Regulation No. 61 of 2023 provides a robust foundation for TB control, its implementation demands further refinements to ensure alignment with good governance principles and the sustainable achievement of TB elimination goals.